2020
DOI: 10.2478/amtsb-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Considerations in Order to Resume Elective Surgery During COVID-19 Pandemic

Abstract: The alarming spread of the novel Coronavirus necessitated the cessation of elective therapeutic procedures in most health-care facilities. This strategy has limited the spread of the virus, but with a huge socio-economic impact. For this reason, the resumption of elective surgery in the context of the coronavirus pandemic is a difficult, but necessary process. Addressing this delicate situation requires interdisciplinary collaboration, so as to ensure high quality medical care for all patients, with considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As the present case showed diffuse hypokinetic wall motion, which is not typical of AMI, and was initially able to summon an ambulance for himself, AMI followed by cerebral infarction deteriorated by hypoxia, based on the embolic etiology, was considered a reasonable cause of the CCI in the present case. [ 1 , 2 ] We could not exclude the possibility of iatrogenic stroke due to the procedures during coronary reperfusion, such as percutaneous coronary intervention and IABP implantation. However, the fact that the coma occurred before hospital arrival and there had been signs of early cerebral infarction on CT at hospital arrival suggested that the stroke had occurred before hospital arrival.…”
Section: Discussionmentioning
confidence: 99%
“…As the present case showed diffuse hypokinetic wall motion, which is not typical of AMI, and was initially able to summon an ambulance for himself, AMI followed by cerebral infarction deteriorated by hypoxia, based on the embolic etiology, was considered a reasonable cause of the CCI in the present case. [ 1 , 2 ] We could not exclude the possibility of iatrogenic stroke due to the procedures during coronary reperfusion, such as percutaneous coronary intervention and IABP implantation. However, the fact that the coma occurred before hospital arrival and there had been signs of early cerebral infarction on CT at hospital arrival suggested that the stroke had occurred before hospital arrival.…”
Section: Discussionmentioning
confidence: 99%